Consanguineous Marriages & Some Reproductive Parameters for Sample from Families in North Africa - الركابي عبد الامير (Iraqi Journal of Science, 2025)
In this study distributed 1320 questionnaire for families in two countries from North Africa ( Libya , Mourtania ) contains some parameters consanguineous degrees, marriage period , fertility degree for families and some reproductive health parameters (parity ,spontaneous abortion , fetal death , still birth and neonatal death 0-2 years).The result refers to the non consanguineous percentage equal 47.1% which considered high when compared with other Arabia countries like Egypt which equal 28.9% for marriages .(18).The non fertile families percentage equal 1.4% also refers to increase parity percentage when compared with other countries in the world and also the Arabia countries.Spontaneous abortion percentage equal 7.2 % which considered high and also it is expected because increase the non related marriages distributed percentage 19.2% considered low if compared with the other Arabia countries like Iraq equal 28.4% .(20) The percentage of genetic diseases in families 18.9% also high related to increase consanguineous marriages also congential malformation for children less than two years old in this families equal 5.9%.